2011
DOI: 10.1007/s12562-011-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

The sinking performance of the tuna purse seine gear with large-meshed panels using numerical method

Abstract: This paper reports an improved version of the numerical method used in a previous study on the dynamic simulation of purse seine gear in three dimensions. The improvement is achieved by refining the mass-spring model to take into account both the drag coefficient as a function of the attack angle and Reynolds number as applied to the setting operation of the purse seine gear. The validity of the numerical simulation is assessed by comparing the measured and calculated values for the sinking depth of the net. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 11 publications
1
24
5
Order By: Relevance
“…It is attributed to the net panels in the bunt section that are made of netting with thicker twine and smaller mesh size. The purse line tension was reported 450 kN at the peak in the simulation by Hosseini et al (2011) and is larger than that in our study. This difference in purse line tension may be due to the structural difference of the nets.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…It is attributed to the net panels in the bunt section that are made of netting with thicker twine and smaller mesh size. The purse line tension was reported 450 kN at the peak in the simulation by Hosseini et al (2011) and is larger than that in our study. This difference in purse line tension may be due to the structural difference of the nets.…”
Section: Discussioncontrasting
confidence: 78%
“…Few studies reported the net geometry and dynamics monitored by underwater acoustic sensors (Misund et al, 1992;Tenningen et al, 2015). Recently, the applications of numerical simulation approach facilitate our understanding of the submerged behavior of the net (Lee et al, 2005;Kim et al, 2007;Kim and Park, 2009;Hosseini et al, 2011;Riziotis et al, 2013). These studies reported the simulated shape and movement of purse seine during shooting and pursing.…”
Section: Introductionmentioning
confidence: 99%
“…where ∀ is the volume of the mass point, and λ is additional mass coefficient. As suggested by Hossenni et al [20], the additional mass coefficient for a sphere is a constant of 0.5; for a cylinder, it is equivalent to the sine function of the angle of attack θ, and is computed as follows:…”
Section: Kinematic Equationmentioning
confidence: 99%
“…Successive research demonstrated the validity of the model with measured data from the sea trial, which evaluated the effects of netting density and sinker weight, among other factors [18]. Owing to effective monitoring and prediction of the net shape in the numerical approach, more details and arguments were put forward, for example, the transformation of the float line and purse line as the seiner drifted toward inside the net circle [19]; the substitution of a large-mesh panel with a prototype for superior performance of sinking and mechanics [20]; and the possibility of controlling the depth of the lower edge of the net by regulating the shooting speed to avoid grounding [21].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al and Cao et al established the dynamic model of the tuna longline, and modelled the space shape distribution and tension distribution in different conditions [15][16] [17]. Zhang et al thought the inertial mass coefficient on knotless netting model used in tuna purse seine is the key factor for sinking performance [18].…”
Section: Introductionmentioning
confidence: 99%